Evaluation Of The Implementation Process Of PSAP 16 Service Concession Agreement – Grantor On Toll Roads At The Ministry Of Public Works And Housing - Stellaria Dyah Prametisiwi; Dwi Martani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to evaluate the process of implementing PSAP 16 in toll road service concession agreements at the Ministry of Public Works and Housing and the obstacles in implementing accounting by applicable regulations. This research uses qualitative methods through a case study approach by analyzing documentation data, process assessment checklists, and semi-structured interviews. The research results show that the implementation process of PSAP 16 has several obstacles, including the computerized accounting calculation system that does not fully accommodate the calculation of service concession assets, especially for service concession agreements that were in place before PSAP 16 came into effect and the need for internal control to separate the portion of capital expenditure and operating expenditure in service concession assets so that it can be presented under economic substance. This research recommends that coordination is needed to develop an integrated accounting system for recording service concession assets, optimize effective internal control over service concession agreements, and adequate measurement mechanisms so that service concession assets shall be accounted for in accordance with PSAP 16.